DNA-Free Genetically Edited Grapevine and Apple Protoplast Using CRISPR/Cas9 Ribonucleoproteins - Malnoy, Mickael; Viola, Roberto; Jung, Min-Hee; Koo, Ok-Jae; Kim, Seokjoong; Kim, Jin-Soo; Velasco, Riccardo; Nagamangala Kanchiswamy, Chidananda (Frontiers in Plant Science, 2016)
The combined availability of whole genome sequences and genome editing tools is set to revolutionise the field of fruit biotechnology by enabling the introduction of targeted genetic changes with unprecedented control and accuracy, both to explore emergent phenotypes and to introduce new functionalities. Although plasmid-mediated delivery of genome editing components to plant cells is very efficient, it also presents some drawbacks, such as possible random integration of plasmid sequences in the host genome. Additionally, it may well be intercepted by current process-based GMO regulations, complicating the path to commercialisation of improved varieties. Here, we explore direct delivery of purified CRISPR/Cas9 ribonucleoproteins (RNPs) to the protoplast of grape cultivar Chardonnay and apple cultivar such as Golden delicious fruit crop plants for efficient targeted mutagenesis. We targeted MLO-7, a susceptible gene (S-gene) in order to increase resistance to powdery mildew (PM) in grape cultivar and DIPM-1, DIPM-2 and DIPM-4 in the apple to increase resistance to fire blight disease. Furthermore, efficient protoplast transformation, the molar ratio of Cas9 and sgRNAs were optimised for each grape and apple cultivar. The targeted mutagenesis insertion and deletion (indel) rate was analysed using targeted deep sequencing. Our results demonstrate that direct delivery of CRISPR/Cas9 RNPs to the protoplast system enables targeted gene editing and paves the way to the generation of DNA-free genome edited grapevine and apple plants.